Pengaruh Pendapatan Asli Daerah (PAD) terhadap Belanja Daerah Pemerintah Kota Balikpapan Tahun 2016-2020 - Salsabila Izzatul Islam; Dyah Ratnawati (Universitas Batanghari, 2022)
This study aims to examine and analyze the effect of local revenue (pad) on the local government expenditure of the Balikpapan City Government in 2016-2020. The population of the Balikpapan City Government APBD Realization Report 2016-2020 sourced from the Balikpapan City Financial and Asset Management Agency (BPKAD). This type of research uses descriptive analysis, this research was conducted by testing descriptive hypotheses. The results of this study indicate that Regional Taxes have no significant effect on Regional Expenditures, Regional Retributions have a significant effect on Regional Expenditures, the results of Separated Regional Wealth Management have no significant effect on Regional Expenditures, and Legitimate Regional Original Income has a significant effect on Regional Expenditures in the Balikpapan City Government.